Occupational Gender Segregation and Social Conflict: Segregation and Credentialism Among Young Workers in Two Occupational Classes - Cattani, Lorenzo (Italian Sociological Review, 2024)
Drawing from social conflict and credentialist theory, we analyze how the field of education influences young women’s chances of access to male-dominated occupations in two occupational classes: professionals and technicians. We further four hypotheses: 1) Women’s default chances of access differ between professionals and technicians. 2) Models of capitalism have little influence over the field of education’s moderation effect. 3) STEM fields of education increase women’s chances of access to male-dominated occupations. 4) Moderation is stronger for male-dominated STEM educational fields. We gather data from the European Labour Force Survey for workers between 25 and 34 years of age and compute logit models for each class. We perform decomposition analysis with the Karlson-Holm-Breen method and then compute logit models with interaction terms. Women’s default chances of access are higher among professionals. The field of education significantly increases women’s chances of access. However, STEM fields such as natural sciences and agriculture, where women represent roughly 50% of graduates, perform worse than male-dominated fields of education such as ICT and Engineering. This is more pronounced among professionals, suggesting that we witness a more substantial reaction to preserving male dominance when women close their gap in opportunities compared to men.